ON THE MODE OF COMMUNICATION OF CHOLERA (REVISITED CLASSICS) - Snow, John (Hygeia - Revista Brasileira de Geografia Médica e da Saúde, 2008)
PREFACE TO THE SECOND EDITIONThe first edition of this work, which was published in August 1849, was only a slender pamphlet. I have, since that time, written various papers on the same subject, which have been read at the Medical Societies, and published in the medical journals. The present edition contains the substance of all these articles, together with much new matter, the greater part of which is derived from my own recent inquiries.I take this opportunity of expressing my thanks to the Registrar-General for the facilities afforded me in making these inquiries.I feel every confidence that my present labors will receive the same kind consideration from the Medical Profession which has been accorded to my former endeavors to ascertain the causes of cholera.Sackville Street, Piccadilly,11 December, 1854.